The simulated clinical environment: Cognitive and emotional impact among undergraduates. (1st February 2017) - Tremblay, Marie-Laurence; Lafleur, Alexandre; Leppink, Jimmie; Dolmans, Diana H. J. M.
Abstract: Context: Simulated clinical immersion (SCI) is used in undergraduate healthcare programs to expose the learner to real-life situations in authentic simulated clinical environments. For novices, the environment in which the simulation occurs can be distracting and stressful, hence potentially compromising learning. Objectives: This study aims to determine whether SCI (with environment) imposes greater extraneous cognitive load and stress on undergraduate pharmacy students than simulated patients (SP) (without environment). It also aims to explore how features of the simulated environment influence students' perception of learning. Methods: In this mixed-methods study, 143 undergraduate pharmacy students experienced both SCI and SP in a crossover design. After the simulations, participants rated their cognitive load and emotions. Thirty-five students met in focus groups to explore their perception of learning in simulation. Results: Intrinsic and extraneous cognitive load and stress scores in SCI were significantly but modestly higher compared to SP. Qualitative findings reveal that the physical environment in SCI generated more stress and affected students? focus. In SP, students concentrated on clinical reasoning. SCI stimulated a focus on data collection but impeded in-depth problem solving processes. Conclusion: The physical environment in simulation influences what and how students learn. SCI was reported as more cognitively demanding than SP. Our findings emphasize the need for the development of adapted instructional design guidelines in simulation for novices.